Non-Neutralizing Antibodies Directed against HIV and Their Functions - Mayr, Luzia M.; Su, Bin; Moog, Christiane (Frontiers in Immunology, 2017)
B cells produce a plethora of anti-HIV antibodies (Abs) but only few of them exhibit neutralizing activity. This was long considered a profound limitation for the enforcement of humoral immune responses against HIV-1 infection, especially since these nAbs are extremely difficult to induce. However, increasing evidence shows that additional non-nAbs play a significant role in decreasing the viral load, leading to partial and sometimes even total protection. Mechanisms suspected to participate in protection are numerous. They involve the Fc domain of Abs as well as their Fab part, and consequently the induced Ab isotype will be determinant for their functions, as well as the quantity and quality of the Fc-Receptors (FcRs) expressed on immune cells. Fc-mediated inhibitory functions such as antibody dependent cellular cytotoxicity (ADCC), antibody dependent cellular phagocytosis (ADCP), aggregation and even immune activation have been proposed. However, as for nAbs, the non-neutralizing activities are limited to a subset of anti-HIV Abs. An improved in-depth characterization of the Abs displaying these functional responses is required for the development of new vaccination strategies, which aim to selectively trigger the B cells able to induce the right functional Ab combinations both at the right place and at the right time. This review summarizes our current knowledge on non-neutralizing functional inhibitory Abs and discusses the potential benefit of inducing them via vaccination. We also provide new insight into the roles of the FcγR-mediated antibody therapeutics in clinical trials for HIV diseases.